1999
DOI: 10.1021/bi991118z
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit Proximity of Residues in the RecA Protein As Shown by Engineered Disulfide Cross-Links

Abstract: Mutational studies of regions that make up the oligomeric interface within the RecA protein filament structure have shown that F217 is an important determinant of RecA function and oligomer stability. All substitutions, other than Tyr and Cys, completely inhibit RecA activities and exhibit a substantial decrease in protein filament stability [Skiba, M. C., and Knight, K. L. (1994) J. Biol. Chem. 269, 3823-3828; Logan, K. M., et al. (1997) J. Mol. Biol. 266, 306-316]. Although the RecA crystal structure exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…From the yeast proteasome structure (PDB entry 1RYP), we identified Pre9 residues that contacted Pre8 and, by sequence alignment, were conserved in Pre6. The β carbons of Pre8‐Lys160 and Pre9‐Leu56 are within 4.9 Å of each other, close to β‐carbon separations seen in natural disulfide bonds (Skiba et al , 1999), so these residues were changed to cysteines.…”
Section: Resultsmentioning
confidence: 62%
“…From the yeast proteasome structure (PDB entry 1RYP), we identified Pre9 residues that contacted Pre8 and, by sequence alignment, were conserved in Pre6. The β carbons of Pre8‐Lys160 and Pre9‐Leu56 are within 4.9 Å of each other, close to β‐carbon separations seen in natural disulfide bonds (Skiba et al , 1999), so these residues were changed to cysteines.…”
Section: Resultsmentioning
confidence: 62%
“…Many studies have shown that the oligomeric state of free RecA protein is exquisitely sensitive to a variety of solution conditions including protein concentration, ionic strength, and temperature and that at the protein concentrations typically used in DNA strand exchange assays, RecA exists as a complex mix of various oligomeric forms (9)(10)(11)(12)(27)(28)(29)(30). The fact that the RecA-FD protein functions both in ViVo and in Vitro demonstrates that dimeric RecA can serve as the nucleating unit for filament assembly onto ssDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Two highly conserved consecutive glycine residues (Karlin & Brocchieri, 1996), critical for RecA function (Hörtnagel et al 1999) and situated at the C-terminal junction between the loop and the protein core may participate in this flexibility (see also De Zutter et al 2001). Based on engineered disulfide cross-linking and mutation studies, residue Phe217 has been proposed to mediate a change in loop conformation via its insertion into a hydrophobic pocket, where it would bind more tightly than in its crystal position (Skiba et al 1999 ;De Zutter et al 2001). Phe217 belongs to the small helix G following loop L2 and close to the nucleotide-binding site (Fig.…”
Section: Transmission Of Structural Information Along the Filamentmentioning
confidence: 99%